Effects of different slaughtering methods on rigor mortis development and flesh quality of tench (Tinca tinca). (24th May 2014) - Gasco, L.; Gai, F.; Rotolo, L.; Parisi, G.
Summary: The effects of different slaughtering methods on rigor mortis and flesh quality parameters were investigated. Eighty tench were divided into four groups, whereby each group was slaughtered using a different method: percussive stunning (PS), live chilling (LC), asphyxia (CO2 ), or electrical stunning (ES). Progression of rigor mortis (RM) was recorded (30 h) as well as pH, colour, cooking losses, texture, drip losses and free water after 24 h of storage at +2°C. The PS group showed a delayed onset of RM when compared to the other groups and with a later beginning of rigor resolution. The highest rigor index values were shown in the PS and CO2 groups, and were reached at 24 and 20 h post‐mortem, respectively. ES fish exhibited a significantly faster rigor onset when compared to the PS group. At 24 h, pH was not affected by the stunning methodology, nor were the colour or texture characteristics, even when a trend was observed (PS>ES>CO2 >LC) for the latter parameter. This research is evidence of how stunning procedures prior to slaughter have a significant effect on rigor mortis development, whereas no differences were found concerning quality parameters.